Planning the Barrio: Ethnic Identity and Struggles over Transit-oriented, Development-Induced Gentrification. (December 2021) - Sandoval, Gerardo Francisco
I argue that ethnic identity formed the basis of collective actions against transit-oriented, development-induced gentrification in three Latino barrios in Oakland, Los Angeles, and San Diego. I demonstrate how these barrios relied on ethnic identity as a basis for mobilizing political capital, grassroots actions, and symbolic capital. Ethnic identity helped Latinos in these barrios create meaningful spaces of participation that transformed these transit investments into community-driven projects and encouraged opportunities for community benefits.